A NEW PROTEOCEPHALUS SANGAMESHWARIENSIS N.SP.(PROTEOCEPHALIDAE : LARUE,1911) CESTODE PARASITE FROM MASTACEMBELLUS ARMATUS AT RATNAGIRI - DANDWATE, R.R.; LONKAR, R.S.; PAWAR, R.G. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
The present communication deals with a new species of the genus Proteocephalus, Weinland. 1958 Protocephalus sangameshwariensis n. sp. It is differentiated from the earlier known species of the genus with the characters like anteriorly conical scolex, five suckers, large neck, testes 140144 in number, W-shaped ovary, vagina thin tube, short receptaculum seminis, rounded ootype, Jok marginal genital pore and granular vitellaria.